Benefits of maternal pectin supplementation in gestation diet on vaginal microbiota of sows and intestinal health of newborn piglets - He, Jiaqi; Zheng, Jie; Huang, Yingyan; Li, Shuang; Hua, Lun; Jiang, Xuemei; Che, Lianqiang; Fang, Zhengfeng; Feng, Bin; Lin, Yan; Xu, Shengyu; Li, Jian; et al. (Frontiers in Veterinary Science, 2024)
Pectin was seen as a proved prebiotics and widely used in human health products. This study aims to assess the impact of dietary pectin supplementation during gestation on sow vaginal microbiota and health of offsprings' intestines. Thirty sows were randomly allocated to two groups to fed a standard diet (CON), or a standard diet supplemented with 3g/kg pectin (PEC). Sow (blood, feces and vaginal swabs) and offspring (blood, intestines issues and colonic contents) samples were collected. The results indicate that the relative abundance of vaginal Lactobacillus was notably enhanced in PEC; fecal βglucuronidase (β-G) activity and plasma 17β-estradiol (E2) concentration were significantly increased in PEC. Newborn piglets were found had different microbial communities as well, at phylum level, Proteobacteria dominated in CON, and Firmicutes dominated in PEC. Newborn piglets in PEC had lower IL-6 concentration in plasma. The expression of intestinal cytokines of offspring was improved as well. Villus height and V/C in PEC were extremely higher than those in CON. In conclusion, dietary pectin supplementation can be benefit to both sows and newborn piglets.